2012
DOI: 10.1186/1471-2407-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic suppression combined with radiotherapy for the treatment of prostate adenocarcinoma: a systematic review

Abstract: BackgroundLocally advanced prostate cancer is often associated with elevated recurrence rates. Despite the modest response observed, external-beam radiotherapy has been the preferred treatment for this condition. More recent evidence from randomised trials has demonstrated clinical benefit with the combined use of androgen suppression in such cases. The aim of this meta-analysis is to compare the combination of distinct hormone therapy modalities versus radiotherapy alone for overall survival, disease-free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This finding has resulted in decreased incidence and severity of rectal adverse events [3,4]. It has also been confirmed that combining HT with EBRT significantly improved not only biochemical control but also survival outcomes compared with EBRT alone [5,6]. These benefits were observed with both short-term (3-6 months) and long-term (>1 year) HT [5].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This finding has resulted in decreased incidence and severity of rectal adverse events [3,4]. It has also been confirmed that combining HT with EBRT significantly improved not only biochemical control but also survival outcomes compared with EBRT alone [5,6]. These benefits were observed with both short-term (3-6 months) and long-term (>1 year) HT [5].…”
Section: Discussionmentioning
confidence: 54%
“…Meanwhile, the survival benefits of adding hormonal therapy (HT) to the standard doses of EBRT had also been confirmed [5,6]. The survival benefit of combining HT with EBRT over EBRT alone was observed in both…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rates of BCR may be reduced with adjuvant or neoadjuvant ADT in carefully selected patients with intermediate- or high-risk localised PCa [1, 73], and the decision to use adjuvant or neoadjuvant ADT with RT in such patients should therefore be based upon individualised assessment.…”
Section: Neoadjuvant and Adjuvant Hormonal Therapy With Rtmentioning
confidence: 99%
“…Hormone therapy, also known as androgen deprivation therapy, can be used to treat prostate cancer after surgery or radiation therapy [1]. However, hormone therapy alone does not eradicate prostate cancer and metastatic prostate cancer does not respond to hormone therapy or chemotherapy [2].…”
Section: Introductionmentioning
confidence: 99%